The investigation on the degree of inhibition of MAC and DEA inhibitors during wax deposition / Nazmin Syahirah Alias - Alias, Nazmin Syahirah (2017)
Deposition of wax can cause a serious problem to the flow of the crude oil in the pipeline. Chemical methods will be applied in the crude oil industry to reduce wax deposition in transportation of crude oil through pipeline in subsea conditions. Maleic Anhydride Copolymer (MAC) and Diethanolamine (DEA) are used in this investigation to estimate the performance as an effective wax inhibitor at different temperature ranging from 5°C to 15°C and concentration ranging from 500 to 5000 ppm using cold finger apparatus equipped with an agitator. 10 mL of MAC and DEA were added into the cold finger apparatus and water bath temperature surrounding the vessel at 50 °C. The deposited wax will be scrapped and weighed. The rotation speed was fixed at 400 rpm. Based on the amount of wax deposit weight, MAC is chosen as the most effective inhibitor compared to DEA. The weight of the wax deposition are able to be reduced when using MAC.